Pengaruh Segmenting dan Targeting terhadap Volume Penjualan Melalui Minat Beli Sebagai Variabel Intervening - Karimah, Sari Yazidhatul; Kumbara, Vicky Brama; Candana, Dori Mittra; Rasyid, Rohsita Amalyah (Jurnal Ekonomi & Bisnis, 2025)
The era of globalization, business competition is very sharp, both in the domestic and foreign markets. Market segmentation (segmenting) and target market determination (targeting) influence the sales volume of a product or service. The main focus of this research is to examine the role of consumer purchase intention as an intervening variable, which acts as a mediator between marketing strategies and sales outcomes. By understanding and implementing appropriate segmentation and targeting strategies, companies can enhance consumers' purchase intentions, which ultimately leads to a positive impact on increasing sales volume. This research aims to test how big the influence of segmenting and targeting is on sales volume through purchase interest as an intervening variable at the classy cafe Rimbo Bujang. The data collection method is through surveys and distributing questionnaires, with a sample of 96 respondents. The analytical method used is structural equation modeling using smartpls. The research results showed that there was a significant influence of segmenting on buying interest. There is a significant influence of targeting on buying interest. There is a significant influence of segmenting on sales volume. There is an insignificant effect of targeting on sales volume. There is a significant influence of buying interest on sales volume. There is a significant influence of segmenting on sales volume through purchasing interest. There is a significant influence of targeting on sales volume through purchasing interest. The R-Square value for the purchase intention variable is 78.2%, indicating that the remaining 21.8% is influenced by other variables outside of this study.